Design and evaluation of a rodent-specific focal transcranial magnetic stimulation coil with the custom shielding application in rats - Liu, Li; Ding, Ming; Wu, Junfa; Zhang, Yuwen; Guo, Shaoqian; Wang, Nianhong; Wang, He; Yu, Kewei; Weng, Yuanfeng; Luo, Lu; Zhang, Jingjun; Zhang, Quan; et al. (Frontiers in Neuroscience, 2023)
Repetitive TMS has been used as an alternative treatment for various neurological disorders. However, most TMS mechanism studies in rodents have been based on the whole brain stimulation, the lack of rodent-specific focal TMS coils restricts the proper translation of human TMS protocols to animal models. In this study, we designed a new shielding device, which was made of high magnetic permeability material, to enhance the spatial focus of animal-use TMS coils. With the finite element method, we analyzed the electromagnetic field of the coil with and without the shielding device. Furthermore, to assess the shielding effect in rodents, we compared the c-fos expression, the ALFF and ReHo values in different groups following a 15 min 5 Hz rTMS paradigm. We found that a smaller focality with an identical core stimulation intensity was achieved in the shielding device. The 1 T magnetic field was reduced from 19.1 mm to 13 mm in diameter, and 7.5 to 5.6 mm in depth. However, the core magnetic field over 1.5 T was almost the same. Meanwhile, the area of electric field was reduced from 4.68 cm2 to 4.19 cm2, and 3.8 mm to 2.6 mm in depth. Similar to this biomimetic data, the c-fos expression, the ALFF and ReHo values showed more limited cortex activation with the use of the shielding device. However, compared to the rTMS group without the shielding application, more subcortical regions, like the striatum (CPu), the hippocampus, the thalamus, and the hypothalamus were also activated in the shielding group. This indicated that more deep stimulation may be achieved by the shielding device. Generally, compared with the commercial rodents’ TMS coil (15 mm in diameter), TMS coils with the shielding device achieved a better focality (~6 mm in diameter) by reducing at least 30% of the magnetic and electric field. This shielding device may provide a useful tool for further TMS studies in rodents, especially for more specific brain area stimulation.